Implementation Regionalization Principle Based on Sanitary and Phytosanitary (SPS) Agreement According to Vienna Convention on the Law of Treaties (1969) - Manalu, Velicia Theoartha; Rosadi, Sinta Dewi; Amalia, Prita (Faculty of Law, Universitas Sebelas Maret, 2021)
The practice of the regionalization principle in Article 6 Sanitary and Phytosanitary (SPS) Agreement is still conflicted. This is because of several cases regarding the members misinterpretation of international guidelines in the regionalization principle, such as India – Agricultural Products and Russia – Pigs (EU). Recently, Coronavirus Diseases 2019 (Covid-19) has been considered to affect animal trade. Such conditions prompt the World Trade Organization (WTO) to recommend the Members to take SPS Measures to protect their domestic market. However, the trade would be inhibited in case the country-wide ban approach is applied. Therefore, this paper discusses the possible SPS measures under the regionalization principle to promote the trade during the pandemic according to WTO decisions from previous cases in line with the VCLT of 1969. The research result shows that the Covid-19 is an obstacle to international trade and makes humans and animals vulnerable to this virus. Consequently, many animal trades have been banned to prevent its spread. To deal with this condition, Indonesia could apply the regionalization principle in Article 6 SPS Agreement. Moreover, the government should update the quarantine law by pointing out the regionalization principle, unlike the zone system rules only applied to animals susceptible to Food Mouth Disease